Values and argumentation in collaborative design. Issue 2 (3rd April 2022) - Le Bail, Chloé; Baker, Michael; Détienne, Françoise
ABSTRACT: We present analyses of interactions produced in meetings concerned with design of artefacts, where core values (i.e., fundamental beliefs of a person or a group) are at stake, focussing on the processes by which debates evolve and are (possibly) resolved during face-to-face elaboration of design solutions. Four groups of four participants were studied during their collaborative design of sustainable neighbourhood projects. We show that in this case, value conflicts are not genuinely resolved, in that participants do not concede with respect to their values within the duration of the meetings. Value conflicts involve renegotiating meanings of design proposals in order to examine their (in)compatibilities, and to determine possible compromises. Participants either try to 'dissolve' value conflicts by transforming them into conflicts on a factual plane, or else they abandon the discussion, maintaining adversarial positions, changing the topic of discussion, without reaching agreement. The study also highlights the importance of participants who spontaneously adopt moderator roles, supporting meaning-making on the plane of values or else shift the debate towards practical considerations. We discuss implications for both collaborative design and participatory design, considering the roles that values play in these processes.